Case Reports Using Continuous Glucose Monitoring: Analysis For Application Of Digitalization In Management Of Diabetes Mellitus: Life Sciences - Saxena, Rajesh; B Singh, Dr. Anurupa; .Singh, Dr. N. P (International Journal of Life Science and Pharma Research, 2023)
Diabetes has emerged as a burgeoning health challenge in the last two decades. Specifically, there is an alarming rate of adult-onset diabetes mellitus, a point of deep concern. Therefore, cohesive steps are essential for the management of symptoms of diabetes mellitus to regulate its prevalence rate globally. Continuous glucose monitoring (CGM) technology can aid in this effort by allowing for safe therapy intensification with HbA1c (hemoglobin-a1c) reduction and by assisting in lowering some of the psychosocial impacts of diabetes. We aim to analyze the application of the digital device Freestyle Libre Pro in the management of diabetes mellitus. Using the FreeStyle Libre Pro CGM system, we analyzed the datasets for eight patients over 14 days. In addition, regular 12-hour data was monitored on a fortnight basis. Two of the eight cases were on insulin, and the rest were administered oral medications for diabetes care. Ambulatory Glucose Profiles, Average Glucose Levels, Time in Range, Time Below Range, Time Above Range, and, afterward, calculation of HbA1c levels were determined for eight patients using the FreeStyle Libre Pro system’s current glucose measurements. We observed that for four patients, the average glucose levels were maintained in range, and for f our patients, the average glucose levels were above range. Regarding Time, four were above range, and four were in range. Our analysis shows that the Freestyle Libre Pro offers an alternative to current CGM devices for professional use as it may aid clinics and patients.